2B4 co-stimulation and dasatinib modulation enhance anti-CD19 CAR-NK-92 cell cytotoxicity - dos Santos, Matheus Henrique; de Azevedo, Júlia Teixeira Cottas; da Silva Januário, Mara Elisama; Schmidt, Dayane de Fátima; Tirapelle, Mariane Cariati; Biggi, Alison Felipe Bordini; Ebrahimabadi, Sima; Silvestre, Renata Nacasaki; Covas, Dimas Tadeu; Calado, Rodrigo T.; Picanço-Castro, Virgínia (Frontiers in Immunology, 2025)
IntroductionChimeric Antigen Receptor (CAR)–based therapies have transformed cancer treatment, especially in hematological malignancies. While the impact of co-stimulatory domains on CAR-T cell efficacy is well established, the optimal signaling modules for CAR-natural killer (CAR-NK) cells remain less defined. Identifying NK-tailored co-stimulatory domains is essential for maximizing CAR-NK cytotoxicity and clinical potential.MethodsUsing the NK-92 cell line as a controlled proof-of-concept platform, we engineered CAR19 constructs incorporating NK-specific co-stimulatory domains, including 2B4 and DAP12. We performed functional assays to quantify cytotoxicity and cytokine production, and conducted transcriptomic profiling to evaluate transcriptional programs associated with each CAR design. To assess pharmacologic modulation, we exposed CAR-NK cells to transient dasatinib treatment and evaluated its reversible effects on CAR signaling and function. In vivo antitumor activity was tested in a xenograft model.ResultsBoth 2B4- and 2B4-DAP12–containing CARs enhanced NK cytotoxic programming as demonstrated by functional assays and transcriptomic signatures. Short-term dasatinib exposure reversibly suppressed CAR-NK effector function but led to enhanced activity upon drug withdrawal. In vivo, 2B4-DAP12 CAR19-NK-92 cells pretreated with dasatinib displayed superior tumor control relative to conventional 4-1BBζ CAR19-NK-92 cells.DiscussionThese results highlight the importance of selecting NK-specific co-stimulatory domains and leveraging reversible Src-family kinase inhibition to optimize CAR-NK performance. The use of NK-92 cells enabled controlled mechanistic dissection of CAR signaling and pharmacologic effects, providing insights with translational relevance for engineering next-generation CAR-NK therapies in primary NK cells.Chimeric Antigen Receptor (CAR)-based therapies have transformed cancer treatment, especially for hematological malignancies. While the choice of co-stimulatory domains is a well-established determinant of CAR-T success, the optimal signaling modules for CAR-natural killer (CAR-NK) cells remain less defined. In this proof-of-concept study, we used the NK-92 cell line as a controlled experimental platform to evaluate CAR constructs incorporating NK-specific co-stimulatory domains, including 2B4 (CD244) and DAP12. Functional assays and transcriptomic profiling demonstrated that 2B4- and 2B4-DAP12–based CARs promoted NK cytotoxic programming. We further explored transient pharmacologic modulation with dasatinib, showing that short-term exposure reversibly suppressed CAR-NK activity but enhanced function upon withdrawal. In vivo, 2B4-DAP12 CAR19-NK-92 cells pretreated with dasatinib achieved superior tumor control compared to conventional 4-1BBζ CAR19-NK-92 cells. These findings underscore the value of different settings of co-stimulatory domains and reversible kinase inhibition as strategies to optimize CAR design. Importantly, by employing NK-92 cells as a proof-of-concept system, this work provides mechanistic insights that will guide the development of next-generation CAR-NK therapies in primary NK cells.